Supercontinuum Generation by Using a Highly Germania-Doped Fiber With a High-Power Proportion Beyond 2400 nm - Zhijian Zheng; Deqin Ouyang; Jinzhang Wang; Chunyu Guo; Jihong Pei; Shuangchen Ruan (IEEE Photonics Journal)
A high-power all-fiber supercontinuum (SC) source in a highly germania-doped fiber (GDF) pumped by a picosecond thulium-doped master oscillator power amplifier (MOPA) system is presented. By further optimizing the length of the GDF, the long-wavelength edge of the wideband flat SC can be broadened to 3 μm. The flat SC has an average output power of 11.62 W and a 3 dB bandwidth of 750 nm. The power proportion beyond 2400 nm is as high as 55.3%. To our knowledge, this SC average output power is the highest from a highly GDF.